2020
DOI: 10.1038/s41598-020-60811-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum sHLA-G: Significant diagnostic biomarker with respect to therapy and immunosuppressive mediators in Head and Neck Squamous Cell Carcinoma

Abstract: Demographic characteristics of study groups. The baseline data of both study groups have been provided in Table 1. We noticed higher frequency of male subjects in both groups in comparison to female subjects. Patients having tobacco consumption habit (62.5%) were more prevalent in the study cohort. Patients with oral cavity site, node involvement, later stages of tumor and MDSCC histopath were more. Estimation of HLA-G, IL-10 and IFN-γ protein level in the study population. By SPR. The standard curves obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…To complete the overview of sHLA-G in cancer, in Table 2 all studies were included that were either performed after 2017 or that were missing in the referenced papers. In summary, most recent studies assessing sHLA-G in the context of solid tumors found increased levels in patient samples [ 5 , 6 , 7 , 32 , 33 , 34 ] ( Table 2 , upper part). A few studies also included non-malignant diseases as their control cohorts [ 35 , 36 , 37 , 38 , 39 ].…”
Section: Shla In Malignanciesmentioning
confidence: 91%
See 2 more Smart Citations
“…To complete the overview of sHLA-G in cancer, in Table 2 all studies were included that were either performed after 2017 or that were missing in the referenced papers. In summary, most recent studies assessing sHLA-G in the context of solid tumors found increased levels in patient samples [ 5 , 6 , 7 , 32 , 33 , 34 ] ( Table 2 , upper part). A few studies also included non-malignant diseases as their control cohorts [ 35 , 36 , 37 , 38 , 39 ].…”
Section: Shla In Malignanciesmentioning
confidence: 91%
“…In a few studies, sHLA-G levels also positively correlated with more advanced disease stage [ 5 , 6 , 7 , 33 , 38 , 45 , 46 ]. In CRC, however, sHLA-G levels were found to have contrasting prognostic values depending on the TNM stage [ 43 ], illustrating that using HLA-G as a solid tumor biomarker may not always be straightforward.…”
Section: Shla In Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of diagnosis, sHLA-G is abnormally expressed in the plasma in breast ductal carcinoma ( 131 ), head and neck squamous cell carcinoma ( 129 ), gastric cancer ( 33 ), CRC ( 125 ), and papillary thyroid carcinoma ( 65 ), which is considered to be a preoperative diagnosis of cancer histopathology potential marker of aggressiveness. It is worth noting that in gastric cancer, researchers have found that sHLA-G in combination with common serum tumor markers, such as CA72-4, CA125, and CA19-1, can improve the clinical screening of gastric cancer compared with sHLA-G alone ( 132 ).…”
Section: Shla-g In the Blood Of Tumor Patients As Circulating Tumor Markersmentioning
confidence: 99%
“…The secreted cytokines include interleukin 10 (IL-10), which might promote T regulatory cell (Treg) suppressive activity or increase the expression of the immunosuppressive molecule like HLA-G. Meanwhile, the transforming growth factor beta (TGF- β ), which has a well-known immunosuppressive role, garners much attention in this field [ 36 40 ].…”
Section: Current Situations and Limitations With Tcr-like Car Targmentioning
confidence: 99%